Customer Satisfaction and Loyalty in Fast-Food MSMEs Influenced by CSR, Social Media, and Perceived Value - Marzuki, Marzuki; Imaningsih, Erna Sofriana (ARE Publisher, 2026)
Objectives: This study aims to analyze the effect of Corporate Social Responsibility (CSR), social media, and perceived value on customer loyalty, with customer satisfaction as a mediating variable in fast-food MSMEs, namely Sukaku Fried Chicken. Methodology: This research employed a quantitative approach using a survey method with purposive sampling. Data were collected from 163 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Finding: The results show that CSR, social media, and perceived value have a significant positive effect on customer loyalty. CSR has no significant effect on customer satisfaction, while social media and perceived value significantly increase customer satisfaction. Customer satisfaction significantly increases customer loyalty and mediates the effect of social media and perceived value on customer loyalty. However, customer satisfaction does not mediate the effect of CSR on customer loyalty. Conclusion: Based on Expectancy Confirmation Theory (ECT), perceived value that consistently meets customer expectations will enhance satisfaction as the primary determinant of loyalty, wherein the influence of social media and perceived value on loyalty occurs through the mediation of customer satisfaction.